A Comparative Study of Patients’ Attitude Before and after Receiving Healthcare Services at Bam Pasteur Hospital - Zahra Shaabani; Parsa Mohammad Alizadeh; Farzaneh Sheikhali; Mohammad Reza Rajabalipour; Mohammad Javad Akbarian Bafghi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The human attitude to events, including health and disease, and his interpretations determinesthe quality of his life. The purpose of this study was to evaluate the attitudes of patients before and afterreceiving the services of Pasteur Hospital in Bam.Methods: This is a descriptive study. The research population included 110 patients referring to men’ssurgery and women’s surgery who were studied by simple sampling method. The attitude of patientsbefore and after receiving healthcare was measured by a researcher-made questionnaire. Data analysis wasperformed using spss24 software Through descriptive and analytical tests such as one-way ANOVA, twopopulation mean comparison and pair comparison statistical tests.Results: The results of statistical tests showed that the average total attitude score of clients after receivingservices (2.58) was more than the mean of attitude of clients before receiving services (2.41) (p=0.017).Paired t-test showed significant relationship between the attitude score of the patients towards medical staffvisitors (p=0.017) and Patient discharge unit (p = 0.001) before and after receiving the service, but nosignificant relationship was found between the other units.Conclusion: It can be concluded that the attitude of the clients after receiving the services has been positive.Therefore, to improve the delivery of services and to increase the satisfaction of clients in some sectors,managers can be more precise planning to improve quality.